ROLE OF KSHARASUTRA IN AXILLARY HIDRADENITIS SUPPURATIVA - A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2015)
Hidradenitis suppurativa is a chronic inflammatory disease on certain areas of the skin, subcutaneous tissues which characterized by the formation of abscesses and sinuses due to primarily an infection of the apocrine group of sweat glands. Hidradenitis suppurativa occurs after puberty, the majority of patients being in the second or third decades of life. In the early stages the disease appears as a firm subcutaneous nodule, suppuration, persists discharge and the affected region may show numerous sinus openings. Management of Hidradenitis suppurativa requires complete surgical excision of the lesion in single or multiple stages, the resulting raw area may be very extensive which was difficult to heal with secondary intension and commonly requires skin graft. Hence, surgical excision for Hidradenitis suppurativa may become challenge and there is a scope to become an alternative as Ksharasutra therapy for hidradenitis suppurativa surgical excision. The present case study of axillary hidradenitis suppurativa was treated with Ksharasutra along with isotretinoin & doxycycline hydrochloride oral medicine. Ksharasutra therapy required 7 sittings (1 sitting conducted every week) to complete excision and epithelialization of tract while doxycycline hydrochloride 100 mg & isotretinion 10 mg once a day orally was continued upto 3 months to control infection & to prevent new nodule formation. Patient was get completely cured from sign and symptom of axillary hidradenitis suppurativa. After that patient was follow up took place for one month for observations.